Leveraging Augmented Reality for Interactive Language Learning - Salamah, Umi; Zaki, Amin; Rokhyanto, Rokhyanto; Razak, Faisal (Journal International of Lingua and Technology, 2024)
The rapid advancement of technology, particularly in augmented reality (AR), has opened new possibilities for interactive language learning. Traditional language learning methods often fail to engage learners actively, limiting the development of real-world communication skills. AR, with its immersive and interactive nature, offers an innovative approach that can bridge this gap by providing contextualized language learning experiences. This research aims to explore how augmented reality can be leveraged to enhance the effectiveness and engagement of language learners in both formal and informal educational settings. A mixed-methods research design was employed, combining quantitative data from language proficiency assessments and qualitative insights gathered through surveys and interviews with both learners and educators. AR-based language learning applications were implemented over a period of three months with a sample of 150 students, and their progress was monitored through pre- and post-tests. Learners interacted with virtual objects, scenarios, and conversations in real-world environments, providing immersive language practice opportunities. The results indicated a significant improvement in language proficiency, particularly in speaking and listening skills, with learners showing increased confidence and engagement. AR-enhanced lessons allowed students to practice language in context, making the learning process more intuitive and enjoyable.